Transformational Leadership of Principals: Driving Excellence in Education Quality - Muhammad Yakob; Tengku Muhammad Sahudra; Sukirno Sukirno (STAI Hubbulwathan Duri, 2025)
Transformational leadership, characterized by vision-driven motivation and innovation, plays a pivotal role in fostering educational improvement. In the school context, principals who apply this leadership style can promote systemic change, enhance teacher engagement, and drive the overall quality of education. This study employed a literature review methodology, analyzing 20 peer-reviewed articles published between 2014 and 2021. Data were gathered using keyword-based searches, applying strict inclusion criteria, and synthesized through thematic content analysis. The data were categorized based on key research questions and interpreted through a multi-step content analysis process. The findings indicate that principals who embody transformational leadership fulfill multiple roles, including educator, manager, administrator, supervisor, innovator, and motivator. Such leaders foster collaboration among schools, communities, and parents, and create inclusive environments that enhance school-community relationships. Their adaptive and participatory leadership style contributes to a strong sense of ownership and belonging among stakeholders. Transformational leadership significantly influences teacher motivation, professional growth, and the creation of a positive work culture. Principals who practice this leadership style inspire staff, provide professional development opportunities, and cultivate a supportive educational climate. Future studies should focus on developing targeted in-service training to strengthen transformational leadership competencies, aiming to enhance educational outcomes at scale.